The optimal ratio of mixed talc silica and Narathiwat clay for cordierite - Mullite refractories - Nattawut Ariyajinno (2018)
© 2018 Trans Tech Publications, Switzerland. In this paper, effects of incorporation of Narathiwat clay (NT), talc and silica on the mechanical properties of cordierite-mullite refractories were investigated. The starting raw materials were mixed in different ratios and fired at 1300oC for 2 hours. XRD patterns of fired refectories indicated cordierite and mullite phases. The fired samples were studied the firing shrinkage, water absorption, bulk density, apparent porosity and bending strength of the cordierite-mullite refractories. The optimum condition was achieved for the composition of 20% Talc that had shrinkage: 11.78%, water absorption: 4.16%, bulk density: 2.28 g/cm3, apparent porosity: 9.2% and bending strength: 330.82 kg/cm2. The results thus showed that Narathiwat clay, talc and silica was a potential materials for as cordierite-mullite refractories.